2021
DOI: 10.1038/s41467-021-24271-w
|View full text |Cite
|
Sign up to set email alerts
|

Fast and strong amplifiers of natural selection

Abstract: Selection and random drift determine the probability that novel mutations fixate in a population. Population structure is known to affect the dynamics of the evolutionary process. Amplifiers of selection are population structures that increase the fixation probability of beneficial mutants compared to well-mixed populations. Over the past 15 years, extensive research has produced remarkable structures called strong amplifiers which guarantee that every beneficial mutation fixates with high probability. But str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 52 publications
1
54
1
Order By: Relevance
“…Typically, amplifiers of selection have also a higher fixation time [27][28][29]. Thus, one has to be careful that the assumption of small mutation rate is still fulfilled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, amplifiers of selection have also a higher fixation time [27][28][29]. Thus, one has to be careful that the assumption of small mutation rate is still fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…In Evolutionary graph theory, evolutionary dynamics on graph structures have been studied in great detail. While the field has been mostly driven from the mathematical and computational community [1, 2, 18, 27, 29], partly driven by biological systems [16, 30, 31], now there is increasing interest in applying these ideas to experimental systems in microbiology [32, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Zhang et al (2011) observed fast evolution of resistance of Escherichia coli to ciprofloxacin within 10 h in a structured heterogeneous environment in a microfabricated device ( Zhang et al, 2011 ). As suggested by theory, the structure of these microfluidics-based environments may act as selection amplifiers for the evolution of resistance ( Tkadlec et al, 2021 ). Other experiments carried out on soft agar plates suggested that motility (surface-associated swarming behavior and swimming) may have an important role in the adaptation and evolution in structured environments ( Lai et al, 2009 ; Butler et al, 2010 ; Baym et al, 2016 ; Ghaddar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major goals of evolutionary graph theory 1 is to assess the effect of underlying population structure on the fixation probability (the probability of ultimate fixation of a mutant) [2][3][4][5][6] and the fixation time [7][8][9][10] . An important aim is to find an optimized structure to speed up or slow down the spread of a newly arising mutant [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%